2020
DOI: 10.3390/brainsci10090584
|View full text |Cite
|
Sign up to set email alerts
|

Apparent False Lateralization of Seizure Onset by Scalp EEG in Temporal Lobe Epilepsy Associated with Cerebral Cavernous Malformation: A Case Report and Overview

Abstract: False lateralization of ictal onset by scalp electroencephalogram (EEG) is an infrequent entity that has been reported in patients with mesial temporal lobe epilepsy associated with hippocampal sclerosis (HS). In these cases, a tendency for rapid seizures that spread through the frontal-limbic system and hippocampal commissural pathways to the contralateral hemisphere has been proposed. Cerebral cavernous malformations (CCMs), which constitute a collection of abnormally configured small blood vessels with irre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In Case 26, scalp EEG might have falsely revealed seizure onset contralateral to the true focus, if the CM in the left amygdala interrupted the propagation of ictal discharges to the ipsilateral neocortex, as it was described in detail in our previous case report [ 11 ]. In the temporal lobe area, ictal discharges are thought to propagate quickly to the contralateral side via the hippocampal commissure or anterior commissure [ 9 , 12 , 16 ]. Asaadi et al reported that 23% of ictal discharges originating from the hippocampus did not spread to the ipsilateral neocortex, but instead spread to the contralateral hippocampus [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Case 26, scalp EEG might have falsely revealed seizure onset contralateral to the true focus, if the CM in the left amygdala interrupted the propagation of ictal discharges to the ipsilateral neocortex, as it was described in detail in our previous case report [ 11 ]. In the temporal lobe area, ictal discharges are thought to propagate quickly to the contralateral side via the hippocampal commissure or anterior commissure [ 9 , 12 , 16 ]. Asaadi et al reported that 23% of ictal discharges originating from the hippocampus did not spread to the ipsilateral neocortex, but instead spread to the contralateral hippocampus [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the cerebral cortex near the CM is the epileptogenic lesion in most cases, some authors have documented cases in which scalp electroencephalography (EEG) showed seizure onset contralateral to the location of the CM [ [7] , [8] , [9] ]. As with other intractable epilepsies, comprehensive diagnosis of the focus from semiology, scalp EEG, positron emission tomography, single-photon emission computed tomography, and neuropsychological assessment is required before epilepsy surgery for CM-associated epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…51 Several studies have suggested that there is bilateral thalamic involvement in unilateral and that this may a worse surgical outcome, although this remains unclear. [52][53][54] Prior literature also includes instances of falsely lateralizing patients with cavernous malformations, 55 as was the case with our Patient #1. For the purposes of this study, it was considered more important to exclude multiple epileptogenic foci rather than focus on temporal lobe epilepsy to evaluate the effect of laterality and contralateral involvement of ANT in the presence of ipsilateral atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, we often observe that the lateralization of epileptic seizure symptoms is not clearly depicted in scalp EEG during either seizure or interictal periods. In addition, seizure semiology and scalp EEG findings sometimes appear diametrically opposed [ 7 , 8 ]. Comprehensive searches for the predicted epileptogenic zone are therefore undertaken using methods such as magnetoencephalography [ 9 ], EEG-fMRI (functional Magnetic Resonance Imaging) [ 10 ], fNIRS (functional Near-Infrared Spectroscopy)-EEG [ 11 ], SPECT (Single Photon Emission Computed Tomography) [ 12 ], and PET (Positron Emission Tomography ) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%